Data associated with, "Methane emissions from gathering and boosting compressor stations in the U.S.: Supporting volume 3: Emission factors, station estimates, and national emissions" - Zimmerle, Daniel; Vaughn, Timothy; Luck, Ben; Lauderdale, Terri; Keen, Kindal; Harrison, Matthew; Marchese, Anthony; Williams, Laurie; Allen, David (Colorado State University. Libraries, 2019)
This section provides an overview of the field campaign for the entire project and the data collected in the field campaign data and during the analysis phase of the project.
This data set contains information gathered for the stations visited during this field campaign.
Energy Institute
Keywords: methane; emission factors; oil and gas; national model